Effect of match importance on salivary cortisol and immunoglobulin A responses in elite young volleyball players - Moreira, A.; Freitas, C. G.; Nakamura, F. Y.; Drago, G.; Drago, M.; Aoki, M. S. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to compare the session ratings of perceived exertion (Session-RPE) responses and the salivary cortisol (sC) and immunoglobulin A (SIgA) levels between a regular season match (RM) and the final championship match (FM) in elite male volleyball players against the same opponent team. Higher importance was assumed for FM because this match would define the championship team. Session-RPE was obtained after 30 minutes of each match using the CR-10 scale. Saliva samples were collected before and after each match and during a rest day (baseline) at the same period of the matches. The SIgA and sC concentrations were measured by enzyme-linked immunosorbent assay. Greater Session-RPE was observed for FM as compared with RM (p < 0.01). The analysis of variance showed greater sC concentrations to FM as compared with RM for both prevalues and postvalues and compared with baseline (p < 0.05). Significant lower SIgA prevalues were noted for FM. In conclusion, the results showed that match intensity, cortisol concentration, and SIgA prelevel were affected by the match importance. These results indicate that monitoring session-RPE, sC, and SIgA responses, in conjunction, during training and competition, would provide valuable informations regarding how athletes cope with sports induced stress. This study provided knowledge about the effect of match importance on salivary markers related to stress that may help coaches to avoid excessive training loads reducing the likelihood to decrements on mucosal immunity and its consequent risk to upper respiratory tract infections, which in turn might affect the performance.